MOBILE INTEGRATED SMART IRRIGATION SYSTEM USING IoT - C M, Avinash; M, Girish; V, Abhishek; S, Manjunath; Kumar R, Shashi (The journal of contemporary issues in business and government, 2021)
Today’s world, the scarcity and usage of water is increasing day by day, it is very much important to conserve water for the future generation. The water requirement is very much needful for irrigation system and at a same time, proper management of water is also very much important with the available sources. Therefore a smart system is essential to manage the same. These papers present a smart system developed for irrigation system using IoT (internet of things). The main purpose of this system is to periodically monitor the soil’s moisture, humidity and temperature levels which are very much required for the crops, based on requirements, the water supply is pumped to the field and at the same time the farmer will receive the real time information to farmer's smart phone.